Crystal structure and enzymatic properties of chalcone isomerase from the Antarctic vascular plant Deschampsia antarctica Desv. - Sun-Ha Park; Chang Woo Lee; Sung Mi Cho; Hyoungseok Lee; Hyun Park; Jungeun Lee; Jun Hyuck Lee (PLOS ONE, 2018)
Chalcone isomerase (CHI) is an important enzyme for flavonoid biosynthesis that catalyzes the intramolecular cyclization of chalcones into (S)-flavanones. CHIs have been classified into two types based on their substrate specificity. Type I CHIs use naringenin chalcone as a substrate and are found in most of plants besides legumes, whereas type II CHIs in leguminous plants can also utilize isoliquiritigenin. In this study, we found that the CHI from the Antarctic plant Deschampsia antarctica (DaCHI1) is of type I based on sequence homology but can use type II CHI substrates. To clarify the enzymatic mechanism of DaCHI1 at the molecular level, the crystal structures of unliganded DaCHI1 and isoliquiritigenin-bound DaCHI1 were determined at 2.7 and 2.1 Å resolutions, respectively. The structures revealed that isoliquiritigenin binds to the active site of DaCHI1 and induces conformational changes. Additionally, the activity assay showed that while DaCHI1 exhibits substrate preference for naringenin chalcone, it can also utilize isoliquiritigenin although the catalytic activity was relatively low. Based on these results, we propose that DaCHI1 uses various substrates to produce antioxidant flavonoids as an adaptation to oxidative stresses associated with harsh environmental conditions.